Two-dimensional conjugated polymer films: Via liquid-interface-assisted synthesis toward organic electronic devices - Liu, Kejun; Wang, Lihuan; Dong, Renhao (Journal of Materials Chemistry C, 2020)
Conjugated polymers have received broad academic and industrial attention for optoelectronic applications. In contrast to linear (one-dimensional, 1D) conjugated polymers, the successive increase of dimensionality by covalently connecting multiple strands towards two-dimensional (2D) conjugated polymers (2DCPs) for organic electronics remains less explored. In this review article, we will summarize the current reports about 2DCPs through liquid-interface-assisted synthesis (LIAS), including Langmuir-Blodgett-assisted synthesis and liquid-liquid interfacial synthesis as well as surfactant-monolayer-assisted interfacial synthesis (SMAIS). Representative synthetic 2DCPs will be introduced, including graphyne, 2D conjugated covalent organic frameworks (2D c-COFs) and 2D conjugated metal-organic frameworks (2D c-MOFs), with emphasis on film synthesis by LIAS. Generally, these synthetic 2DCP films are intrinsic (semi-)conductors with tunable band gaps and possess high crystallinity, large-area, free-standing and single-/multi-layer features, which make processing and electronic device integration facile. To this end, we will discuss the application studies of 2DCP films in field-effect transistors (FETs), memristors and photodetectors, including the description of the device fabrication and unique performance. Finally, challenges and perspectives are provided regarding the future development of LIAS methods toward 2DCP films with diverse structural and functional control as well as the existing key questions for organic electronic devices.
CRIS-Team Scopus Importer:2022-04-14